1995
DOI: 10.1111/j.1574-695x.1995.tb00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of lipopolysaccharide-induced tumor necrosis factor production by cyclosporin A in mice primed with muramyl dipeptide

Abstract: The effect of cyclosporin A (CsA) on tumor necrosis factor (TNF) or interleukin‐6 (IL‐6) production was evaluated in vivo in primed or unprimed mice challenged with lipopolysaccharide (LPS). Both pretreatment with BCG infection or with muramyl dipeptide (MDP) prior to LPS challenge resulted in an increase in the cytokine bioactivity level in the blood. CsA administration inhibited the TNF production. In unprimed mice, either normal or sensitized to LPS lethality by galactosamine treatment, a marked decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…IL-1ra partially antagonized LPS-induced cytokine release in monocytes from BCG-treated individuals (21). TNF-␣ gene expression and blood levels of TNF-␣ are also upregulated by BCG treatment in mice (22,23). In fact, serum levels of TNF-␣ after an intraperitoneal injection of LPS were over 200 times higher in mice that had been inoculated with BCG 2 weeks before than in uninfected mice (18).…”
Section: Discussionmentioning
confidence: 99%
“…IL-1ra partially antagonized LPS-induced cytokine release in monocytes from BCG-treated individuals (21). TNF-␣ gene expression and blood levels of TNF-␣ are also upregulated by BCG treatment in mice (22,23). In fact, serum levels of TNF-␣ after an intraperitoneal injection of LPS were over 200 times higher in mice that had been inoculated with BCG 2 weeks before than in uninfected mice (18).…”
Section: Discussionmentioning
confidence: 99%
“…Pettipher et al (1996) also found that propranolol had the same effect as adrenalectomy, suggesting that effects of adrenalectomy on TNF-a were due to loss of adrenaline, not Cort. Other groups found that adrenalectomy either increased (Le Contel et al 1995) or had no effect (Morrow et al 1993, Meltzer et al 2003 on LPS-induced plasma TNF-a. With respect to IL-6, several groups reported that adrenalectomy increases LPS-induced plasma IL-6 (Morrow et al 1993, Schöbitz et al 1993, Le Contel et al 1995.…”
Section: ###mentioning
confidence: 99%
“…Other groups found that adrenalectomy either increased (Le Contel et al 1995) or had no effect (Morrow et al 1993, Meltzer et al 2003 on LPS-induced plasma TNF-a. With respect to IL-6, several groups reported that adrenalectomy increases LPS-induced plasma IL-6 (Morrow et al 1993, Schöbitz et al 1993, Le Contel et al 1995. However, two of these studies did not examine whether Cort could reverse the effects of adrenalectomy (Morrow et al 1993, Le Contel et al 1995.…”
Section: ###mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, previous studies in humans and mice have shown that CsA could inhibit the pro-inflammatory cytokines IL-1β, IL-6, IL-8, TNF-α, and IFN-γ and increase the production of anti-inflammatory cytokines IL-4 and IL-10 in response to LPS stimulation [19,[59][60][61][62][63][64]. Recently Hu and colleagues, using a pregnant rat model, have demonstrated that CsA significantly ameliorates the clinical signs of LPS-induced pre-eclampsia and inhibits the inflammatory response [59].…”
Section: Introductionmentioning
confidence: 99%